2013
DOI: 10.1073/pnas.1317049110
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia in cirrhosis induces transcriptional regulation of myostatin by an NF-κB–mediated mechanism

Abstract: Loss of muscle mass, or sarcopenia, is nearly universal in cirrhosis and adversely affects patient outcome. The underlying cross-talk between the liver and skeletal muscle mediating sarcopenia is not well understood. Hyperammonemia is a consistent abnormality in cirrhosis due to impaired hepatic detoxification to urea. We observed elevated levels of ammonia in both plasma samples and skeletal muscle biopsies from cirrhotic patients compared with healthy controls. Furthermore, skeletal muscle from cirrhotics ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
320
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 241 publications
(342 citation statements)
references
References 38 publications
18
320
2
2
Order By: Relevance
“…The muscle-to-fat volume ratio also decreased in GS-KO/M mice but to a lesser extent (not shown). In agreement, expression of myostatin, which induces muscle loss, (13) had increased 1.4-fold in GS-KO/L muscle (Fig. 1C).…”
Section: Biometry Of Gs-ko/l Micesupporting
confidence: 79%
See 2 more Smart Citations
“…The muscle-to-fat volume ratio also decreased in GS-KO/M mice but to a lesser extent (not shown). In agreement, expression of myostatin, which induces muscle loss, (13) had increased 1.4-fold in GS-KO/L muscle (Fig. 1C).…”
Section: Biometry Of Gs-ko/l Micesupporting
confidence: 79%
“…Another novel finding is that chronic GS deficiency, in particular that in liver, decreases whole-body muscle-to-fat ratio and increases myostatin expression in muscle, as in cirrhosis of the liver and hyperammonemia. (13) A recent study of similar liver-specific GS-deficient mice (15) showed that mild but chronic hyperammonemia also causes cerebral oxidative stress and behavioral changes. Although both studies observed a similar 2-fold increase in blood ammonia concentration in mice with a hepatic GS deficiency, they differed in basal blood ammonia concentration, which was >5-fold higher in the C57Bl6 mice that Qvartskhava et al (15) used than in the FVB mice we used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present longitudinal study also supports this, as shown in the results, which indicate that the stage preceding sarcopenia is mainly a normal body composition, and the stage preceding sarcopenic obesity is mainly visceral obesity. Although the causes for this and the suppression of secondary sarcopenia that accompanies cirrhosis are unknown (17), at the present time, nutritional therapy, such as high-protein meals that are intended to maintain albumin, the administration of BCAA formulations, and the night-time administration of light meals, is suggested to be helpful (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with results of a study by Tsien et al of 53 deceased brain donor liver transplantation (DDLT) recipients; of these, only 2 of 33 patients with sarcopenia pre-DDLT (defined on the basis of the sum of the psoas, para-spinal and abdominal wall muscles to L4 muscles obtained by CT) had a post-DDLT recovery, while 75% (15 patients) of the non-sarcopenic patients developed this condition pre-DDLT (13), possibly due to a post-DDLT upregulation of myostatin, a potent mediator of muscle depletion, high levels of which seem to be linked to hyperammonemia in patients with ESLD (14).…”
mentioning
confidence: 99%